Efektivitas Sistem Manajemen Iklan dan Promosi di Platform E-commerce Berbasis Business Intelligence: Suatu Perspektif Mahasiswa - Kania Fauziah; Airin Triyana; Zul Azmi (Yayasan Almanar Pujud, 2025)
The digital transformation has shifted business promotion strategies from conventional methods to Business Intelligence (BI)-based advertising management systems on e-commerce platforms. This study aims to examine the perceptions of students at Universitas Muhammadiyah Riau regarding the effectiveness of BI-based advertisement and promotion systems, focusing on their understanding, relevance, and the impact on purchasing decisions. Using a descriptive quantitative approach, questionnaires were distributed to 40 active students who are regular users of e-commerce platforms. The findings reveal that most students have a positive perception of the recommendation system's accuracy, the relevance of ads to personal needs, and the influence of ads on their shopping behavior, with average scores above 3.7. However, students’ understanding of how BI systems work remains moderate, with an average score of 3.2. These results highlight a gap between technology usage and digital literacy. Therefore, educational efforts are necessary to enhance users’ comprehension of the systems they interact with. This study contributes to the development of more human-centered and educational e-commerce promotional systems.